Assessment of Impulse Noise Hazard and the Use of Hearing Protection Devices in Workplaces where Forging Hammers are Used - MŁYŃSKI, Rafał; KOZŁOWSKI, Emil; ADAMCZYK, Jan (Archives of Acoustics, 2014)
The impulse noise is agent harmful to health not only in the case of shots from firearms and the explosions of explosive materials. This kind of noise is also present in many workplaces in the industry. The paper presents the results of noise parameters measurements in workplaces where four different die forging hammers were used. The measured values of the C-weighted peak sound pressure level, the A-weighted maximum sound pressure level and A-weighted noise exposure level normalized to an 8 h working day (daily noise exposure level) exceeded the exposure limit values. For example, the highest measured value of the C-weighted peak sound pressure level was 148.9 dB. In this study possibility of the protection of hearing with the use of earplugs or earmuffs was assessed. The measurement method for the measurements of noise parameters under hearing protection devices using an acoustical test fixture instead of testing with the participation of subjects was used. The results of these measurements allows for assessment which of two tested earplugs and two tested earmuffs sufficiently protect hearing of workers in workplaces where forging hammers are used.